The clinical and pathological significance of borderline T cell–mediated rejection. Issue 5 (22nd January 2019) - Nankivell, Brian J.; Agrawal, Nidhi; Sharma, Ankit; Taverniti, Anne; P'Ng, Chow H.; Shingde, Meena; Wong, Germaine; Chapman, Jeremy R.
Abstract : The pathological diagnosis of borderline rejection (BL‐R) denotes possible T cell–mediated rejection (TCMR), but its clinical significance is uncertain. This single‐center, cross‐sectional cohort study compared the functional and histological outcomes of consecutive BL‐R diagnoses (n = 146) against normal controls (n = 826) and acute TCMR (n = 55) from 551 renal transplant recipients. BL‐R was associated with the following: contemporaneous renal dysfunction, acute tubular necrosis, and chronic tubular atrophy ( P  < .001); progressive tubular injury with fibrosis by longitudinal sequential histology (45.3% at 1 year); increased subsequent acute rejection (39.4%), allograft failure ( P  < .001), and patient mortality ( P  = .007). BL‐R detected by biopsy indicated for impaired function was followed by suboptimal functional recovery (46.3%), persistent inflammation (27.2%), and acute rejection episodes (50.0%) despite antirejection treatment in 83.3%. By 1 year after BL‐R, the incidence of new‐onset microvascular inflammation (9.3%), C4d staining (22.3%), transplant glomerulopathy (13.3%), and de novo donor‐specific antibodies (31.5%) exceeded normal controls ( P  < .05‐.001). BL‐R inflammation in protocol biopsy persisted in 28.0% and progressed to acute rejection in 32.6%; however, it resolved in 61.6% of the untreated cases. In summary, BL‐R is a heterogeneous diagnostic grouping, ranging from mild inconsequential inflammation to clinically significant TCMR, which is capable of immune‐mediated tubular injury resulting in inferior functional, immunological, and histological consequences. Abstract : This study of borderline T cell–mediated rejection biopsies found that this heterogeneous diagnostic category leads to inferior functional, immunological, and histological outcomes, as well as reduced graft survival.